Acute generalised exanthematous pustulosis: An update - Abhishek De; Sudip Das; Aarti Sarda; Dayamay Pal; Projna Biswas (Wolters Kluwer Medknow Publications, 2018)
Acute generalised exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction and is attributed to drugs in more than 90% of cases. It is a rare disease, with an estimated incidence of 1-5 patients per million per year. The clinical manifestations characterised by the rapid development of sterile pustular lesions, fever and leucocytosis. Number of drugs has been reported to be associated with AGEP, most common being the antibiotics. Histopathologically there is intraepidermal pustules and papillary dermal oedema with neutrophilic and eosinophilic infiltrations. Systemic involvement can be present in more severe cases. Early diagnosis with withdrawal of the causative drug is the most important step in the management. Treatment includes supportive care, prevention of antibiotics and use of a potent topical steroid.